Complex conductivity dependent surface plasmon polaritons at the interface of metal and silver silica nanocomposites. Issue 3 (2nd November 2021) - Ullah, Kaleem; Bacha, Bakht Amin; Wahid, Umer; Ullah, Arif; Irfan, Muhammad
Abstract: Surface plasmon polariton (SPPs) is investigated with complex conductivity at the interface of metal and silver silica nonacomposites. The amplitude and phase of complex conductivity significantly influence the SPPs propagation. The value of Re(ksp ) varies with the phase and norm of complex conductivity. Similarly the wavelength, propagation length, group velocity, decay time, penetration depth and rotary Plasmon drag of SPPs are investigated. These results may have vital applications in the field of wave‐guides, Plasmonster, data storage, chemical and biosensors. Abstract : Surface plasmon plays a key role with multiple applications in plasmonics. Plasmonster is a three‐terminal device such as the transistor with the property of rapid data transmission of photonic devices. A conductive layer is placed on electro‐optical materials to provide the interface necessary for surface plasmon polariton propagation. Conductivity increases plasmonster sensitivity and improves sensor sensitivity.